A Comparative Study of Carbon Storage in Two Cocoa (Theobroma cacao) Shade-Types and a Teak Plantation in the Moist Semi-deciduous Forest Zone of Ghana. - Eunice Nimo; Evans Dawoe; John Tennyson Afele (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2021)
on life, it is important that steps are taken to mitigate its effects. With the intensification of cocoa production, there has been a shift in traditional cocoa farming over the years leading to the removal of shade trees, hence, removal of carbon sinks. This study was carried out to compare the amount of carbon stored in cocoa ecosystems to that of a 20 years teak plantation and to calculate the trade-off of carbon between the two systems. Cocoa farms of similar ages (20 years) were selected in which three-subplots were demarcated on each farm at Piase in the Bosomtwe District. Tree Diameter at Breast Height (DBH) was measured and soils samples were collected and analyzed for organic carbon percentage and bulk density. One-way Analysis of Variance was used to analyze above and belowground tree carbon and two-way analysis of variance was used to analyze soil organic carbon stored. Teak plantation recorded higher carbon stock (739.33±2.24 Mg C.ha-1) compared to full sun cocoa (9.36±2.24 Mg C.ha-1). Soil organic carbon across the three farms showed significant (p = 0.0010) variations with depths. The 0-20 cm soil depth stored significantly more (p = 0.0000) organic carbon compared to 20-40 cm soil depth. Total soil carbon stored revealed significant differences amongst the various farms with the full sun (40.857±0.52 Mg C.ha-1) being the least whilst the teak plantation stored the highest (72.42±0.52 Mg C.ha-1). Total carbon (above-ground tree carbon + below-ground tree carbon + soil organic carbon) showed significant difference (p= 0.0000) between land use types with shaded cocoa farm (74.3±0.89 Mg C.ha-1), full sun cocoa farm (32.02±0.89Mg C.ha-1) and that of the teak plantation (950.91±0.89 Mg C.ha-1) respectively. Traditional cocoa ecosystem (shaded cocoa farms) has the potential to store carbon significantly higher than that of the full sun systems.